The effect of mineral fertilisation on water chemistry of carp ponds - K. Fasaic; L. Debeljak; Z. Adamek (Acta Ichthyologica et Piscatoria, 1989)
The basic physico-chemical parameters of the water were studied in the experimental fish ponds of “Draganici” (Yugoslavia) during the rearing season of the 1985. The particular attention was taken to the changes of amounts of dissolved O2 and NO3-, NH4+ and PO43- ions in the water under the conditions of fertilised experimental ponds by the mineral fertiliser NPK with the formula of 17 : 8 : 9. The concentration of oxygen in fertilised ponds increased in the middle of rearing season by 2 to 129%, while at the and it decreased by about 20% in comparison with non-fertilised ponds. The need for phosphates was not shown in September, but the necessity of nitrates was evident during the whole period under study. The significant increase occurred in amount of NH4+ after fertilisation, but already after the second day the application of fertilisers it constantly decreased.